The reliability and factor analysis validity of a new instrument to measure Illusion of Control bias in What-If DSS production scheduling simulation - Zakaria, Halimi; Al - Sagoff, Syed A. Kadir; Ali@Ibrahim, Azizi (2008)
There are several methods of accessing illusion of control that have been used by researchers.Many researchers have measured Illusion of Control (IOC)through questionnaire in experimental situations where subjects need to self report their confidence levels.The instrument developed in this paper is a 7-point Likert-styled questionnaire used together with a Decision Support System (DSS) in a production scheduling simulation has been reliability tested and factor analyzed for validity as a new instrument to measure illusion of control.